Inovasi Pemerintah Kota Semarang Dalam Penanganan Corona Virus Disease (Covid-19) - Zahratul Aeni; Teuku Afrizal (Universitas Medan Area, 2022)
This study analyzes public policy innovations regarding the prevention and control of Covid-19 as a new policy innovation to contain the spread and growth of Covid-19 cases. This is expected to be able to analyze policy innovations that can accelerate the handling of the Covid-19 problem. This research was conducted in Semarang City based on Nugroho's (2015) theory of quality policy (2015). The research method uses a qualitative approach with literature study analysis techniques using data collection techniques by searching various secondary data sources in the form of government documents, electronic mass media reporting with the keyword search for innovation in the application of Covid-19 response policies. The results of this study found that since the implementation of this new innovation policy, there has been an increase in the cure rate of 77.09% of the total confirmed cases and a decrease in the risk of spreading so that the City of Semarang is in PPKM (Enforcement of Community Activity Restrictions) Level 1 with low risk. One of the contributors to the number of Covid-19 cases is immigrants from outside the city of Semarang who reached 45% of new positive cases. The high mobility of the movement of people outside the city of Semarang entering the city of Semarang and the low level of control and supervision of the movement of the arrival of residents outside the city of Semarang who enter the city of Semarang who carry the virus must be a major concern in controlling the rate of increase in Covid-19 in the city of Semarang.